Soil physical quality changes under different management systems after 10 years in the Argentine humid pampa - J. L. Costa; V. Aparicio; A. Cerdà (Solid Earth, 2015)
South American countries with the highest surface of land under no-tillage (NT) management are Brazil, Argentina and Chile. In Argentina, 78.5% of the agricultural land is cropped under NT management. Several experiments have confirmed the improvements in soil aggregation and infiltration achieved by NT management in dry-land farming areas associated with increases of bulk density (δb) under NT management. An increase in bulk density implies a reduction of the macro and mesoporosity that is in contradiction with the increased infiltration that occurs at macro and mesopores. We hypothesize that the increase of bulk density in NT management mainly affects the mesopores. We evaluated the evolution of the soil physical parameters in three management systems in four farmers' fields. We found that the reduction in total porosity under NT management is mainly a product of a reduction in the percentage of mesopores in the soil. In this work, the results indicate a modification of some soil physical parameters (porosity, near-saturated hydraulic conductivity, soil structure) due to uninterrupted agricultural production, but the management system did not affect the yields of crop.